New nutritional data on selected traditional foods from Black Sea area countries - Costa, H.S. (2011)
Traditional foods are the key elements that differentiate the dietary patterns of each country. In most countries, there is limited information on the nutritional composition of such foods, therefore, there is a need to investigate, register and promote traditional foods. These foods are also a valuable contribution to the development and economic sustainability of rural areas and preservation of biodiversity. One of the aims within BaSeFood project is to provide new data on the nutritional composition of traditional foods of plant origin from six Black Sea area countries (Bulgaria, Georgia, Romania, Russian Federation, Turkey and Ukraine) to promote their sustainable development and exploitation. Thirty-three traditional foods were selected per food group and country taking into account namely food biodiversity and food composition data. Chemical analyses to determine the nutritional composition of the selected traditional foods were performed and the data were fully documented and evaluated according to EuroFIR guidelines and standardised procedures. To assure the quality of analytical results accredited laboratories or laboratories with successful participation in proficiency testing schemes were chosen. Information on food description, recipe, ingredients, sampling plan, sample handling, component identification, method specification, value and quality assessment was collected for each of the traditional foods for inclusion in the available national food composition databases. The use of a common methodology for the study of traditional foods will enable countries to further investigate their traditional foods and to continue to update their national food composition databases. Moreover, knowledge base of traditional foods from Black Sea Area countries will contribute to promote local biodiversity and sustainable diets, by maintaining healthy dietary patterns within local cultures.